Simultaneous determination of dopamine, ascorbic acid and uric acid with electrospun carbon nanofibers modified electrode - Liu, Yang; Huang, J.; Hou, H.; You, T. (Elsevier Inc., 2008)
A novel carbon-nanofiber-modified carbon-paste electrode (CNF-CPE) was employed for the simultaneous determination of dopamine (DA), ascorbic acid (AA) and uric acid (UA) with good selectivity and high sensitivity. The CNFs were prepared by combination of electrospinning technique with thermal treatment method and were used without any pretreatment. In application to determination of DA, AA and UA in the ternary mixture, the pristine CNF-CPE exhibited well-separated differential pulse voltammetric peaks with high catalytic current. Low detection limits of 0.04 µM, 2 µM and 0.2 µM for DA, AA and UA were obtained, with the linear calibration curves over the concentration range 0.04–5.6 µM, 2–64 µM and 0.8–16.8 µM, respectively.